Effect of Curcumin Nanoemulsions Stabilized with MAG and DAG-MCFAs in a Fructose-Induced Hepatic Steatosis Rat Model - Beatriz Agame-Lagunes; Peter Grube-Pagola; Rebeca García-Varela; Alfonso Alexander-Aguilera; Hugo S. García (MDPI AG, 2021)
Current changes in diet, characterized by an increase in the intake of sweetened beverages, are heavily related to metabolic disorders such as non-alcoholic fatty liver. This condition can produce simple steatosis and, in worse cases, potentially result in steatohepatitis, fibrosis, and cirrhosis, comparable to the damage caused by the consumption of more or less 20-30 g of alcohol per day. The main objective of this research was to evaluate the effect of curcumin (Curcuma longa) nanoemulsions, using mono- and diacylglycerides medium chain fatty acids as stabilizers in an in vivo hepatic steatosis rat model. Pathology was induced by providing 30% fructose intake in the drinking water. Globule sizes under 200 nm that were stable for 4 weeks were obtained; curcumin encapsulated in the nanoemulsion was >70%. The results revealed an improvement regarding body and liver weight in the animals treated with curcumin nanoemulsions. A decrease in total cholesterol, LDL, AST/ALT, and HDL in serum was observed; however, no apparent improvement regarding serum glucose or triacylglycerides values was noted. Histological analysis showed a significant decrease in the extent of steatosis, inflammation, and brown adipose tissue in the treated animals.